“PIBER LEDFRESUR” (PENANGKAPAN IKAN BERBASIS LED DAN FREKUENSI SUARA) - Hermawati Hermawati; Adil Adil; Muhammad Nurjumadil; Jamaluddin Jamaluddin (Jurnal Pendidikan Teknologi Pertanian, 2018)
The condition of fishery resources in Barru Regency can still be categorized as good fishery and not yet widely used, due to lack of adequate fishing catch fisheries. One of the locations of fishing operations in Barru namely Mallusetasi waters. The dominant fishing gear used in fishing operations in Barru include seine trawl, fishing rod, gill net, tap chart and floating chart but still not giving optimal result. the goal in this program is the application of LED-based fishing technology and the determination of the frequency of sound can be useful for the fishermen community and increase the number of catch and environmentally friendly. This activity is divided into 3 stages namely the initial stage (preparation), the stage of implementation, and the final stage all of which was carried out approximately for 5 months. PKM has a promising potential both in terms of knowledge and its application. PIBER LEDFRESUR during its application gives effect to the number of fisherman catch and the amount of compression / economy of new bojo fishermen in new regency. With the use of PIBER LEDFRESUR the energy used is relatively small as well as the most gterpenting environmentally friendly. The catch of a fisherman usually 1 capture in 4 hours now using FIBER LEDFRESUR rose to 4 times in 4 hours, with a catch of 20 kg per catch